1997
DOI: 10.1007/s002709900103
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of radiological and surgical placement of central venous catheters

Abstract: Radiological placement is consistently more reliable than surgical placement. There are fewer placement complications and fewer catheter infections overall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
34
1
5

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(41 citation statements)
references
References 20 publications
1
34
1
5
Order By: Relevance
“…Williams [25] reported 24.5 mSv/1000 cGy cm 2 for the fingers during IR procedures, which is slightly lower than the value found in this study (35.6 mSv (1000 cGy cm 2 ) -1 averaged for the left and right finger). Vano et al [14] reported 33-60 mSv/1000 cGy cm 2 for the left eye during IC procedures, which is higher than the value of 13.7 mSv/1000 cGy cm 2 found in this study; however, the authors state that the use of protective shields during the intervention was irregular, thus higher doses to the physicians are to be expected.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Williams [25] reported 24.5 mSv/1000 cGy cm 2 for the fingers during IR procedures, which is slightly lower than the value found in this study (35.6 mSv (1000 cGy cm 2 ) -1 averaged for the left and right finger). Vano et al [14] reported 33-60 mSv/1000 cGy cm 2 for the left eye during IC procedures, which is higher than the value of 13.7 mSv/1000 cGy cm 2 found in this study; however, the authors state that the use of protective shields during the intervention was irregular, thus higher doses to the physicians are to be expected.…”
Section: Discussioncontrasting
confidence: 54%
“…Continuing advances in digital imaging have enabled new and complex operations to be implemented, such as vascular and hepatobiliary interventional procedures, that were seldom performed in the past. Improvements in catheters, guidewires and stents have contributed to worldwide popularity and expansion of IR [2,3]. Similarly, the number of interventional cardiology (IC) procedures over the last 10 years has also increased rapidly [4].…”
mentioning
confidence: 99%
“…We have also removal removed four ports because of due to systemic infection. The puncture of the subclavian vein is connected associated with pneumothorax in 0.6-4.3% of patients in all the published studies [3,5,15] and some publications were no evidence of any difference in the incidence of pneumothorax [6]. We have founded found rate of pneumothorax 5 (3.4%) in SV group, 2 (1.2%) in JV group.…”
Section: Discussionmentioning
confidence: 53%
“…Using these techniques increases the success rate and decreases complications such as pneumothorax, hematothorax, perforation of the blood vessel, and catheter malposition [1][2][3][4]. Moreover, placement in a radiology suite is reported to be easier to schedule, reduces the time required, and is cheaper [5,6].At our institute, Hickman catheters (HCs) have been placed by radiologists in a radiology suite designed for invasive procedures since 1991. Despite an observed higher technical success rate and lower mechanical complication rate in HC placement, infections were felt to be our most common complication.…”
mentioning
confidence: 99%